Pontine glioma extending to the ipsilateral cavernous sinus and Meckel's cave: MR appearance. - Yuh, W T; Nguyen, H D; Mayr, N A; Follett, K A (American Journal of Neuroradiology, 1992)
The authors describe an exophytic glioma of the pons that grew into the Meckel's cave and cavernous sinus in a 75-year-old man. Pontine gliomas should be included in the differential diagnosis of a hyperintense, complex cystic mass seen along the distribution of cranial nerve V.